PERCEPTIONS OF STUDENTS OF TRANSLATION STUDIES TOWARDS THE ROLE OF TRANSLATION COMPETENCE IN CAREER PRACTICE (Journal of Foreign Language Studies, 2024)
This paper is part of a larger multi-faceted project that evaluates the impact of translation competence on the translators’ work outcomes from various perspectives. The paper particularly reports the perceptions of the students of Translation Studies at the University of Foreign Languages, Hue University (HU-UFL) towards the role of translation competence in career practice. Accordingly, recommendations are proposed to improve the Translation Studies training program at the English Department, HU-UFL.The data were collected through questionnaires and analyzed statistically. The findings indicate that students have not been fully aware of the system of knowledge, skills and strategies essential for future professional development, which causes them many difficulties in their practice. The findings also point out some considerations for developing the Translation Studies training program at HU-UFL, which serve as a reference for similar training programs.
Keywords: translation competence; Translation Studies; perceptions